Diagnostic challenges in pulmonary Langerhans cell histiocytosis: A case report of nodular presentation in an adult - Nouman Aziz; Waseem Nabi; Sukhrob Makhkamov; Sadhna Kumari; Dimitri Chepkunov; Daye Chung; Sonu Sahni (Respiratory Medicine Case Reports, 2025)
Adult pulmonary Langerhans cell histiocytosis (PLCH) represents a poorly understood subset of LCH, primarily involving young to middle-aged smokers and accounting for approximately 3–5 % of adult diffuse lung diseases. This case report presents uncommon presentation of adult PLCH with nodular pulmonary lesions on a 40-year-old female with a history of asthma, systemic lupus erythematosus (SLE), and smoking. CT chest confirmed multiple bilateral pulmonary nodules, with the largest measuring up to 12 mm. Biopsy of the lung nodules demonstrated Langerhans cell infiltration, with immunohistochemical staining positive for CD1a and S100, confirming the diagnosis of PLCH. The report underscores the importance of considering PLCH in the differential diagnosis of pulmonary nodules, particularly in patients with a significant smoking history, and contributes to the growing body of knowledge regarding the diverse presentations of LCH in adults.